Plant Diversity and Utilization of Medicinal Plants by Traditional Healers - Rattanapotanan, Natenapa (Naresuan University Journal: Science and Technology (NUJST); Vol 27 No 1 (2019): January - March 2019, 2019)
The research was a survey of the diversity of medicinal plants in the Polsongkram Community Forest, Nonsung District, Nakhon Ratchasima, in tandem with a qualitative research program to assess of these medicinal plants and products, conducted by interviewing local medicinal healers.      The diversity survey was carried out in 2015 and 2016, resulting in the identification of 18 species and 21 families of medicinal plants in the Polsongkram Community Forest, with 23 different medicinal plants identified, mostly in the family Caesalpiniaceae and Dipterocarpaceae. A diversity index of 0.91, with an evenness index of the plants of 0.29, were calculated. Sindora ( Sindora siamensis Teijsm. ex Miq.) is the most important contribution to these indices, and has been long considered to be an important medicinal plant for the ecological system and a very influential plant for the community forest, having been traditionally used for producing medicinal products for health care by the local healers, who have created and are producing 20 medicinal products. This study is an important contribution to the raising of the local people’s self-awareness in conserving and increasing the sustainability of the medicinal plants in their community. Keywords : variety of herb biodiversity, local intelligence, medicinal plants